Minimally invasive versus open pancreatic enucleation. Systematic review and meta‐analysis of surgical outcomes. Issue 7 (25th March 2018) - Guerra, Francesco; Giuliani, Giuseppe; Bencini, Lapo; Bianchi, Paolo P.; Coratti, Andrea
Abstract : Parenchymal sparing procedures are gaining interest in pancreatic surgery and recent studies have reported that minimally invasive pancreatic enucleation may be associated with enhanced outcomes when compared with traditional surgery. By meta‐analyzing the available data from the literature, minimally invasive surgery is not at higher risk of pancreatic fistula and offers a number of advantages over conventional surgery for pancreatic enucleation.